Implementation of Mahārat Al-Lughah Learning Methods and Their Implications for Santri’s Arabic Language Proficiency at Darussalamah Al-Mubarok Islamic Boarding School - Jannah Salsabila; Endan Hamdan Ridwan; Hilman Mubarok (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to describe the implementation of the Mahārat Al-Lughah learning method and its implications for the Arabic language ability of santri at Pondok Pesantren Darussalamah Al-Mubarok Cianjur. This research uses a qualitative descriptive approach because it focuses on understanding the learning process, language activities, obstacles, and changes experienced by santri in a natural pesantren setting. Data were collected through observation, interviews, and documentation involving santri who participated in Mahārat Al-Lughah activities, Arabic language mentors, and pesantren administrators. The findings show that the implementation of Mahārat Al-Lughah learning is carried out through vocabulary reinforcement, listening practice, simple conversation, Arabic text reading, writing exercises, and language habituation in the pesantren environment. The method supports the development of santri’s Arabic ability in listening, speaking, reading, and writing. Its implications are seen in increased confidence, courage to speak, better vocabulary mastery, and improved understanding of Arabic texts. However, several obstacles remain, including limited vocabulary, different initial abilities, fear of making mistakes, and inconsistent use of Arabic outside formal activities.